Seventeen-Year Journey Working With a Master - Zhu, Jinfang (Frontiers in Immunology, 2018)
It had been a great honor for me to work with the late Dr. William E. Paul for seventeen years in the Laboratory of Immunology (LI) from 1998 until his passing in 2015. He was such a master in the immunology field. Under his outstanding guidance, my research has been focusing on transcriptional regulation of T helper (Th) cell differentiation, especially, the role of a master transcription factor GATA3 on Th2 cell differentiation. Just as enormous scientific contributions of Dr. Paul (we all call him Bill) to the immunology community are far beyond his serving as the Chief of the LI, GATA3 also plays important roles in different lymphocytes at various developmental stages besides its critical functions in Th2 cells. In this special review dedicated to the memory of Bill, I will summarize the research that I have carried out in Bill's lab working on GATA3 in the context of related studies by other groups in the field of T cell differentiation and innate lymphoid cell (ILC) development. These include the essential role of GATA3 in regulating Th2/ILC2 differentiation/development and their functions, the critical role of GATA3 during the development of T cells and innate lymphoid cells, and dynamic and quantitative expression of GATA3 in controlling lymphocyte homeostasis and functions.